Estudo demográfico do câncer de cólon e reto no estado de Sergipe - Torres Neto, Juvenal da Rocha (2008)
In Brazil, the colorretal cancer (CRC) was the fifth cause of death for cancer in men and fourth, in women in the period of 1995-1999. However, there are few registers on the epidemiologicals aspects of this pathology in Sergipe, being this the focus of this study. OBJECTIVE: To catalogue all CRC cases diagnosed in Sergipe in the period of 03 years (2003-2005), tracing a demographic study. METHOD: The data had been harvested in findings of all pathological anatomy laboratories on the state. RESULTS: The CRC was more frequent in women (n=201; 56,62%) than in men (n=154; 43,38%). The average age was 60,27 years old, and 39 (10,99%) had up to 40 years old. Adenocarcinoma was the histology type more found, present in 295 (83,10%) patients. In Sergipe, the incidence of CRC in 2003, 2004 and 2005 was 4,57; 4,72 and 5,29 per 100.000 men and, 6,07; 5,57 and 6,98 per 100.000 women respectively. In the capital, in this respectives years, these numbers had increased to 10,25; 10,57 and 10,29 per 100.000 men and 12,92; 13,16 and 15,07 per 100.000 women. CONCLUSIONS: The achieved data are similar to the ones of the literature, showing an increase in the annual incidences of the neoplasm.